Pelaksanaan Aplikasi Instrumentasi di SMA Negeri se-Kabupaten Pati - Chairunnisak, Fitriani; Mugiarso, Heru (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
The study was based on the phenomena of lack of implementation of instrumentation applications in school that are at the level sufficient at this stages of planning, implementation, evaluation, analysis of the results, and reporting. This prompted researchers to conduct research on instrumentation application. The goal of this study was to investigate the implementation of instrumentation application in phases planning, implementation, evaluation, analysis of the results, and reporting. Type of thisresearch is descriptive survey method. The population is all of teachers guidance and counseling in Senior High School at Pati regency by using the study population because the population only 28 people in 8 schools. Data method useing the questionnaire. Instrument validity using the product moment formula. Reliability is use alpha formula. The data analysis used descriptive percentage. The result showed the following picture;instrumentation from the stage of planning, implementation, evaluation, analysis of result and report the results of a percentage of 57% (medium). It pointed out that counselor in Senior High School at Pati less understanding of implementing application, because it is on the e criteria.